Studi Eksperimental mengenai Pengaruh Komposisi Media Taman terhadap Pertumbuhan Kacang Hijau (Vigna Radiata) - Hani’ Amari’a; Muhammad Suwignyo Prayogo; Asiatul Hafsoh; Dita Ragil Prasetya Ersa (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2025)
This study aims to analyze the effect of planting media on the growth of mung bean (Vigna radiata). The experimental research used three types of planting media: ordinary soil, compost, and rice bran, over a three-week period starting from April 1, 2025. Observations were made every three days to measure plant height and leaf count. The results showed that plants grown in compost media exhibited the fastest growth compared to those grown in ordinary soil and rice bran. At the end of the observation period, plants in compost reached 18.0 cm with 11 leaves, plants in ordinary soil reached 16.0 cm with 10 leaves, and those in rice bran reached 15.5 cm with 10 leaves. Plants in compost showed more consistent and significant growth throughout the observation period. Meanwhile, plants in ordinary soil and rice bran grew slower but still developed well. This study provides information about the effectiveness of different planting media in supporting mung bean growth. These findings can be applied to improve mung bean cultivation by selecting optimal planting media in various farming conditions.